Divorce Bureaucracy in the Sharia Space: Examining Practices in Langsa City, Aceh - Muhazir Muhazir; Azwir Azwir (At-Tafkir, 2024)
Divorce in the community is often understood differently between Islamic law, the State, and customary law. Each of these laws has a fundamental legal basis regarding the concept of divorce. The impact of differences in the legal concept of divorce results in different Muslim communities in the process of terminating marital relations. This research aims to examine further how the divorce bureaucracy in Indonesia affects the divorce process in the community. This paper results from an empirical study with a socio-legal study approach, this approach is used to review how divorce in society is practiced. Data was obtained from interviews with relevant parties. To strengthen the data and analysis, this research also uses several empirical research results and other important articles related to this paper. The results show that the divorce bureaucracy in Langsa City, Aceh still leaves problems caused by differences in viewpoints and interests so that divorce outside the court still occurs. The difference in perspective is based on the understanding that divorce is legal if it fulfills the provisions of Islamic law. On the other hand, people who are aware of the law have the view that divorce must be done before the court. The bureaucracy of divorce, which involves administration and the conditions that must be met, makes divorce considered complicated and takes a long time. Conversely, religious divorce does not require a long time and cost. In addition, the interest in a quick process without the need for an administrative process also influences the divorce bureaucracy. Non-judicial mediation at the village level is essential for reducing divorce rates and reducing divorce bureaucracy.